Investigation of vitamin B12 biosynthesis by known and newly identified bacterial strains - Dudko, Darya; Justus Liebig University Giessen (My University, 2023)
Vitamin B12 (cobalamin) is an essential nutrient playing an important role in many crucial processes in the human body. Due to such essential requirement, the demand for vitamin B12 and thereby interest in alternative efficient vitamin B12 sources is growing. The importance of vitamin B12 became clear in the 1920s after two American physicians, Minot and Murphy, demonstrated the role of their so-called “extrinsic factor” in the treatment of pernicious anemia. After years of further research, the complete chemical synthesis of cobalamin was achieved by Woodward and Eschenmoser in 1972. However, due to the very complex chemical structure of vitamin B12, the described synthesis procedure included about 70 steps, which makes it economically disadvantageous. For this reason, microbial synthesis is used as the exclusive strategy for industrial vitamin B12 production nowadays. Although there are several vitamin B12 - producing bacterial species known, there are differences in the type of the compound synthesized by different strains. For example, Propionibacterium freudenreichii (formerly P. shermanii) is well known for its ability to synthesize the active form of vitamin B12, while production of a vitamin B12 analogue called pseudovitamin B12 was shown for Lactobacillus species. The two forms differ in their chemical structure, which makes pseudovitamin B12 inactive as a cofactor for human enzymes. Hence, if the goal is to produce vitamin B12 for human nutrition purposes, it is important to determine the type of the cobalamin synthesized by the microorganisms. Various methods of vitamin B12 analysis have been described, which differ in their sensitivity and ability to discriminate between the vitamin B12 forms. The classical microbiological assay (MBA) is known to respond not only to vitamin B12 but also to its analogues, while HPLC - based methods possess the required specificity. In this work, a sensitive and reliable LC-MS/MS method for the identification and quantification of vitamin B12 was developed which not only allows vitamin B12 quantification, but also enables clear discrimination between its active and inactive form. The developed method was successfully applied for the quantitative comparison of the well - known vitamin B12 - producing species and for the analysis of the active vitamin B12 production in the newly selected candidate strains. Different strategies for the identification of new producing bacterial strains were proposed in this work which resulted in the description of bacteria with the ability to selectively produce high levels of active vitamin B12 under aerobic conditions. Among the identified strains, Terrabacter sp. DSM 102553 and Hyphomicrobium sp. DSM 3646 proved to be the most promising cobalamin-producing strains. Cobalamin synthesis with the identified bacteria in different media was investigated, which resulted in identification of low-cost media enabling accumulation of high vitamin B12 yields. The relatively high vitamin B12 concentrations achieved with the strains in simple cultivation experiments performed in low-cost media open new opportunities for a cost-effective biotechnological vitamin B12 production.
Keywords: vitamin B12; pseudovitamin B12; cobalamin; LC-MS; ddc:500; ddc:570